2019
DOI: 10.3390/v11121156
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Characteristics of a Porcine Astrovirus Strain Isolated in China

Abstract: Astroviral infection is considered to be one of the causes of mammalian diarrheal diseases. It has been shown that astrovirus infections cause varying degrees of diarrhea in turkeys and mice. However, the pathogenesis of porcine astrovirus is unknown. In this study, the virulence of a cytopathic porcine astrovirus (PAstV) strain (PAstV1-GX1) isolated from the PK-15 cell line was tested using seven-day-old nursing piglets. The results showed that PAstV1-GX1 infection could cause mild diarrhea, growth retardatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…A previous surveillance study conducted by our group found a high percentage of coinfection among diarrheic piglets (9). PAstV, which has been identified as an important agent of diarrhea (10), and frequently presents as a coinfection with other porcine pathogens (3,5,6,9,11). However, data regarding coinfections with PAstV in diarrheic piglets in China are limited.…”
Section: Introductionmentioning
confidence: 85%
“…A previous surveillance study conducted by our group found a high percentage of coinfection among diarrheic piglets (9). PAstV, which has been identified as an important agent of diarrhea (10), and frequently presents as a coinfection with other porcine pathogens (3,5,6,9,11). However, data regarding coinfections with PAstV in diarrheic piglets in China are limited.…”
Section: Introductionmentioning
confidence: 85%
“…The results of the preferred codons were consistent with those of the nucleotide composition analysis. 6) codons, respectively. PCA results showed that the first two principal axes accounted for 41.9% and 24.6% of the total variation of RSCUs ( Figure S1).…”
Section: Rscu Patterns Of Pastvmentioning
confidence: 99%
“…PAstV-3 is found in tissues from the central nervous system of piglets and sows with encephalomyelitis and neural necrosis [4,5]. Infection of piglets with PAstV-1 could cause mild diarrhea, growth retardation, and damage to the villi of the small intestinal mucosa [6]. PAstV-4 was detected in the nasal swabs [7] and the feces of pigs [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decade, with the aid of improved sequencing techniques such as high-throughput sequencing, increasing novel clades of astroviruses have been discovered ( 31 ). For quite some time, PAstV was considered as a low-pathogenic virus causing a short-term mild diarrhea ( 32 , 33 ). However, emerging cases of PAstV associated enteritis or polioencephalomyelitis were reported and attracted public attention in recent years ( 8 , 9 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the infection rates of pigs at lactation and nursery stage were also higher than those of grown pigs ( Table 2 ). Pathogenic studies have shown that PAstV infection could cause diarrhea and growth retardation, which could lead to economic losses and cannot be ignored in large-scale pig industries ( 32 , 33 ). Moreover, coinfections of PAstV with other swine viruses were also reported, which pointed out that PAstVs were more intended to co-infect with other viruses, and immunosuppressive viruses such as CSFV could benefit from the replication of PAstV ( 13 , 14 , 43 ).…”
Section: Discussionmentioning
confidence: 99%